Diagnosing fiscal distress: Regional evidence from Polish municipalities - Magdalena Ziolo (Romanian Journal of Fiscal Policy (RJFP), 2015)
The paper deals with the problem of municipalities' fiscal distress and its diagnosis. The study examines the key financial indicators of Polish municipalities located in the West Pomeranian Region and uses them to build an aggregate measurement to identify the level of these municipalities' fiscal distress. The analysis is based on taxonomy methods in order to group the municipalities according to increasing risk of fiscal distress. Based on the aggregated results, ratings for these municipalities have been created. The municipalities have subsequently been classified into three groups: fiscally distressed, fiscally stable, and fiscally neutral. The data set covers the period from 2008-2013 and encompasses 106 municipalities.
Keywords: H7; H12; G01; 330; fiscal distress; municipalities; self-government; public finance; crisis